2013
DOI: 10.1039/c2sm26633d
|View full text |Cite
|
Sign up to set email alerts
|

Peptide functionalized nanoparticles for nonviral gene delivery

Abstract: Much attention has been directed toward improving nonviral gene delivery in order to replace viral vectors and overcome the barriers to clinical gene therapy. Specifically targeting nonviral gene delivery vehicles to the disease tissue can significantly improve their delivery efficiency. Targeting peptides have been developed for growth factor receptors, integrins and tumor vasculature to target cancer, neurotrophin or neurotoxin receptors aiming to give specificity for neurodegenerative disease, airway epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 191 publications
0
57
0
Order By: Relevance
“…To date, there is preclinical evidence that RGD peptides as αvβ3 integrin antagonist can successfully block osteoclast-mediated osteolysis in animal models of bone metastases and some of them have advanced to clinic [21,23]. On the other hand, RGD peptides conjugated drug delivery system targeting αvβ3 integrin for targeted tumor theragnostics has been also well documented in animal models of primary tumors [24,25]. There is, however, lack of results concerning with therapeutic efficacy of such drug delivery system in treating bone metastases..…”
Section: Introductionmentioning
confidence: 98%
“…To date, there is preclinical evidence that RGD peptides as αvβ3 integrin antagonist can successfully block osteoclast-mediated osteolysis in animal models of bone metastases and some of them have advanced to clinic [21,23]. On the other hand, RGD peptides conjugated drug delivery system targeting αvβ3 integrin for targeted tumor theragnostics has been also well documented in animal models of primary tumors [24,25]. There is, however, lack of results concerning with therapeutic efficacy of such drug delivery system in treating bone metastases..…”
Section: Introductionmentioning
confidence: 98%
“…In particular, short peptide chains have attracted a great deal of attention in recent years because of their tunable functionality, biodegradability, and relative ease of synthesis. [20][21][22] It has been shown that short peptide sequences (e.g. RGD and IL-13) can be used for targeting nanoparticles to specic cancer cell lines.…”
Section: -11mentioning
confidence: 99%
“…These drug-loaded particles are then loaded into the polymer solution prior to extrusion as with other types of solution extrusion. Much research has been done in the area of gene therapy to find the best nonviral way to escort genetic sequences into a cell (Khalil et al, 2006;Levine et al, 2013), and intracellular or nuclear delivery is the most challenging area of drug delivery. Normally, for drug-loaded nanoparticles, the entire nanoparticle is released from the fiber while still encapsulating the drug.…”
Section: Protection Methods For Solution Spinningmentioning
confidence: 99%